CattleReview. (2nd January 2019) - Barrett, David C
Abstract : Introduction: This edition of Cattle Review considers papers on the use of recently developed technology to monitor rumen health, the aetiology of digital dermatitis and the on-farm storage of medicines on dairy farms. Highlighting also an initiative to promote veterinary surgeons and farmers working together to remove inappropriate medicines from farm medicine stores.